2021
DOI: 10.1007/s00216-021-03519-w
|View full text |Cite
|
Sign up to set email alerts
|

Laser-induced graphene electrodes for electrochemical ion sensing, pesticide monitoring, and water splitting

Abstract: Laser-induced graphene (LIG) has shown to be a scalable manufacturing route to create graphene electrodes that overcome the expense associated with conventional graphene electrode fabrication. Herein, we expand upon initial LIG reports by functionalizing the LIG with metallic nanoparticles for ion sensing, pesticide monitoring, and water splitting. The LIG electrodes were converted into ion-selective sensors by functionalization with poly(vinyl chloride)-based membranes containing K + and H + ionophores. These… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 79 publications
0
10
0
Order By: Relevance
“…Sodium ionophore, NaTPB, PVC, and DOS (1%, 0.55%, 33%, 65.45%) for a total mass of 100 mg were dissolved in 660 μL of THF and gently sonicated in an ultrasonic bath for ∼3 min to fully homogenize the ion selective membrane (ISM) in a procedure developed for previously reported potassium and ammonium ISM's. 65 ISM was applied to freshly prepared LIG working electrodes in 5 μL coats. Three coats were applied to avoid pinhole formation, and large bubbles were gently dissipated with a needle.…”
Section: ■ Conclusionmentioning
confidence: 99%
“…Sodium ionophore, NaTPB, PVC, and DOS (1%, 0.55%, 33%, 65.45%) for a total mass of 100 mg were dissolved in 660 μL of THF and gently sonicated in an ultrasonic bath for ∼3 min to fully homogenize the ion selective membrane (ISM) in a procedure developed for previously reported potassium and ammonium ISM's. 65 ISM was applied to freshly prepared LIG working electrodes in 5 μL coats. Three coats were applied to avoid pinhole formation, and large bubbles were gently dissipated with a needle.…”
Section: ■ Conclusionmentioning
confidence: 99%
“…[220] Meanwhile, Kucherenko et al reported the versatile LIG platform functionalized with metallic NPs for ion sensing, pesticide monitoring, and water splitting. [221] The fabrication of multifunctional sensors included thermal decomposition of nickel(II) acetate tetrahydrate and an electroless deposition method for Pt, as shown in Figure 13a. For the application of EMI shielding, [92] the LIG-Fe 3 O 4 composite obtains the EMI shielding effectiveness of 32.7 dB.…”
Section: Other Applicationsmentioning
confidence: 99%
“…Biosensors for pesticides were created [ 98 ] by functionalizing LIG electrodes with the enzyme horseradish peroxidase. They showed a high level of sensitivity to atrazine (28.9 na/μm) with little difference from other common herbicides (glyphosate, dicamba and 2,4-dichlorophenoxyacetic acid).…”
Section: Graphene Nanomaterials In Biosensorsmentioning
confidence: 99%